The Contribution of Social Media as a Strategy in Promoting a Sustainable Development for a Balance Ecosystem in the Bangsamoro Area, Philippines - Jawad Salic (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this generation social media is the paramount means of communication to establish social information among societies. This study sought to assess the aid of social media ad as an approach in stimulating sustainable development for a balance ecosystem in the Bangsamoro, Philippines. This study used a structured survey questionnaire that was prepared by the researcher in three pages, distributed to the respondents and did personal interview which was one on one talk with the respondents. Out of six hundred copies of the questionnaire disseminated, five hundred eighty-three (583) were retrieved which represented a response rate of 97.167%. The study has shown that majority of the respondents’ response on social media is very useful in promoting workable progress for a stable ecosystem that can be resulted in establishing an Islamic Financing Institution and a Conventional Financing Institution in the Bangsamoro. This study recommends among Bangsamoro people with knowledge in Islamic economics to create an association that will constantly promote Islamic economics principle through social media.